IMPLEMENTASI PROGRAM INDONESIA’S FORESTRY AND OTHER LAND USE (FOLU) NET SINK 2030 DI PROVINSI RIAU - Mahardika, Moh. Alif Hanif; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Climate change has become one of the major global environmental issues that has encouraged the establishment of various international cooperation mechanisms aimed at reducing greenhouse gas emissions. One of the most significant global agreements is the Paris Agreement, which encourages member states to reduce emissions through commitments known as Nationally Determined Contributions (NDC). Indonesia has responded to this commitment by developing the Indonesia’s Forestry and Other Land Use (FOLU) Net Sink 2030 as a key strategy in the forestry and land-use sector. Riau is one of the strategic regions for the implementation of this program due to its extensive forest, peatland, and mangrove ecosystems, while at the same time facing significant pressure from deforestation. This research employs a qualitative method with a descriptive approach through document analysis of regulations, government reports, and relevant environmental policy literature. The study applies the perspectives of Green Politics, international regime theory, and the state level of analysis to understand the relationship between global commitments, national policies, and their implementation at the regional level. The findings indicate that the implementation of the FOLU Net Sink 2030 program in Riau Province is carried out through various regional policy instruments, such as the Riau Hijau Program, the formulation of the Subnational FOLU Net Sink Work Plan, the strengthening of social forestry, forest and land rehabilitation, peatland restoration, and the protection of mangrove ecosystems. These efforts demonstrate a process of internalizing global climate regime commitments into local policies through synergy between the central government and regional authorities. However, the implementation of the program still faces several challenges, including high deforestation pressure due to plantation expansion, forest and peatland fires, and limited governance capacity at the regional level. Nevertheless, Riau’s ecological potential makes the province strategically important in supporting the achievement of Indonesia’s national net sink target by 2030. Keywords: FOLU Net Sink 2030, Green for Riau, Climate Change, Paris Agreement